1C.07: PRONEUROTENSIN INDEPENDENTLY PREDICTS CARDIOVASCULAR DISEASE. THE MALMÖ PREVENTIVE PROJECT. (June 2015) - Fawad, A.; Schultz, C.; Nilsson, P.M.; Orho-Melander, M.; Melander, O.
Abstract : Objective: Neurotensin is released from the gut after fat intake and has a role in appetite regulations. Proneurotensin is a stable fragment of the neurotensin precursor hormone and fasting plasma proneurotensin levels have shown to be significantly associated with the development of cardiovascular disease in middle aged participants of the Malmö Diet and Cancer Study. Here, we aimed at replicating the initial findings in an independent second cohort and to extend its validity to an older population. Design and method: Malmö Preventive Project (MPP) is a Swedish population based prospective study which comprised 18240 subjects for reexamination in 2002–2006. Fasting proneurotensin was measured in plasma from a random sample of 4804 participants (Age 69 SD (6, 2), 68% Male). Multivariate Cox proportional hazard models adjusted for age, sex, use of antihypertensive medications, systolic blood pressure, BMI, current smoking, high density lipoprotein cholesterol (HDL-C), LDL-C, history of diabetes were used to relate the log transformed levels of fasting proneurotensin to the risk of first fatal or non-fatal cardiovascular event (myocardial infarction or stroke) in the mean follow up time of up to 6.5 years. Results: There were 456 cardiovascular events observed in the study. Hazard ratios (HR) for CVD were expressed per 1 (SD) increment of log transformed proneurotensin for cardiovascular disease as HR 1, 102; 95% CI; 1, 006–1, 088; P = 0, 037. In addition, proneurotensin was divided in to quartiles where quartile 1 defined as (Ref = 1). The risk of CVD was 1, 107(0, 848–1, 444), 1, 349 (1, 040–1, 749), 1, 336 (1, 016–1, 757) in quartile 2–4 when compared with the reference quartile (P for trend = 0.013). Conclusions: Fasting proneurotensin levels are independently associated with the risk of developing cardiovascular disease which replicates the findings in MDC study.